Seed preservatives properties of Secamone afzelii (Schult) K. Schum extracts on wheat grains damage and germination capability - Adesina, J. M. (2023)
The outcomes of the study showed that S. afzelii leaves extracts exhibited significant effect (p < 0.05) in suppressing R. dominica adult emergence and weight loss of wheat grains than untreated. The increase in the concentrations led to significant decrease in adult emergence and weight loss with different extracts. Secamone afzelii ethyl acetate and hexane extracts significantly subdued adult emergence in contact toxicity (6.69% and 8.49%) and fumigant toxicity (8.85 and 8.87); a similar trend was observed in weight loss in both contact (2.33% and 5.13%) and fumigant (1.50% and 1.03%) toxicities at 200 µl, respectively. None of the extracts hinder the germination of treated grains, while germination percentage ranged between 88.69% and 93.40%.